Togo : Technical Assistance Report: Launch of the Project for Strengthening Public Financial Management. (IMF Staff Country Reports; Country Report ;, 2013)
This article discusses the mission to strengthen the financial system of the Republic of Togo. The European Union Delegation and the Fiscal Affairs Department of the IMF signed a technical agreement with the Togolese government. According to the project, a communication program and a training strategy was established, and works have begun to improve budget execution, accounting, finance report, cash management, and so on. The purpose of this mission was to evaluate the government's public finance, but it needs some improvements to attain a perfect form.